2014
DOI: 10.1037/neu0000071
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal brain pathology predicts adverse attention and processing speed outcomes in very preterm and/or very low birth weight children.

Abstract: Objective This study aimed to examine attention and processing speed outcomes in very preterm (VPT; <32 weeks' gestational age) or very low birth weight (VLBW; <1500 g) children, and to assess the ability of brain abnormalities measured by neonatal magnetic resonance imaging (MRI) to predict outcome in these domains. Methods A cohort of 198 children born <30 weeks' gestational age and/or <1250 g and 70 term controls were examined. Neonatal MRI scans at term equivalent age were quantitatively assessed for whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 84 publications
3
81
0
2
Order By: Relevance
“…The scoring system on which this study was based has been used in 2 studies examining the relationships between TEA MR imaging and cognitive outcomes at 7 years. 24,25 Our results support previous findings at TEA and suggest that the brain changes associated with adverse cognitive outcomes are already present as early as 29 to 35 weeks PMA. 7 Of all MR imaging subscale scores, at early and term MR imaging, DGM demonstrated the strongest relationship with outcome.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The scoring system on which this study was based has been used in 2 studies examining the relationships between TEA MR imaging and cognitive outcomes at 7 years. 24,25 Our results support previous findings at TEA and suggest that the brain changes associated with adverse cognitive outcomes are already present as early as 29 to 35 weeks PMA. 7 Of all MR imaging subscale scores, at early and term MR imaging, DGM demonstrated the strongest relationship with outcome.…”
Section: Discussionsupporting
confidence: 90%
“…22 At TEA, global brain abnormality scores were significantly associated with motor outcomes at 2-years CA 23 ; and cognitive outcomes, at 7 years. 24,25 Deep gray matter scores were significantly associated with poorer attention and processing speeds, memory, and learning. 24,25 With safe earlier MR imaging now possible with MR compatible incubators, valid scoring systems for use earlier than TEA are required.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Proactive school entry attention and executive function supports directed at children with the high biomedical, social or developmental risk thus have the potential to optimize early school learning trajectories. Advances in functional neuroimaging have revealed that this vulnerability can be lessened by proactive evidence based interventions [20,21]. In this way we can then ensure that all vulnerable preterm children who enter kindergarten have the health and developmental supports that optimize learning and school success.…”
Section: Where Do We Go Next?mentioning
confidence: 99%
“…It is important to identify early problems within each of these elementary skills, so as to intervene and potentially limit more generalized cognitive deficits. 5 In Brazil, follow-up studies on children born prematurely have been conducted. [6][7][8][9][10][11] However, little information on outcomes from children with neonatal morbidity is available, including on its repercussions on cognitive development and its associations with less favorable socioeconomic and care conditions.…”
Section: Introductionmentioning
confidence: 99%